Alkylation of N-substituted-2-phenylacetamides - Mijin Dušan Ž.; Mišić-Vuković Milica M.; Petrović Slobodan D. (Journal of the Serbian Chemical Society, 2004)
Various N-substituted phenylacetamides were alkylated using different alkylating agents under neutral and basic conditions. Reactions were performed at different reaction temperatures and in various solvents. Also, a number of various catalysts were used including phase-transfer catalysts. Reactions were followed using GC or GC-MS technique and the presence as well as the yields of the alkylation products were established. Generally, the best yield and high selectivity in the studied reactions were achieved under basic conditions where in the certain cases some products, mostly N-product were obtained solely in quantitative yields.